2013
DOI: 10.1002/mana.201200225
|View full text |Cite
|
Sign up to set email alerts
|

The derivative of the parallel volume difference

Abstract: In this paper we continue the investigation of the asymptotic behavior of the parallel volume in Minkowski spaces as the distance tends to infinity that was started in [8] and [9]. Our main result is that the derivative of the difference between the parallel volume of the convex hull of a planar body and the parallel volume of the body itself tends to 0 for r → ∞ at order r −2 . We will use this result to examine Brownian paths and Boolean models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Proof. Kampf proved in [15], lemma 28, that for every compact set A there exists a constant C which depends on n, A so that for every t ≥ 1,…”
Section: In Dimension N ≥mentioning
confidence: 99%
See 1 more Smart Citation
“…Proof. Kampf proved in [15], lemma 28, that for every compact set A there exists a constant C which depends on n, A so that for every t ≥ 1,…”
Section: In Dimension N ≥mentioning
confidence: 99%
“…2 by a convex body B = rB n 2 + M , for some r > 0 and some convex body M such that its support function h B (u) = max{< x, u >, x ∈ B} is twice differentiable on R n \{0} because inequality (6) of [15] holds with these assumptions.…”
Section: The Preceding Theorem Is Still Valid If One Replaces B Nmentioning
confidence: 99%
“…We discuss mainly the parallel volume of finite sets, which turns out to be already nontrivial, but Theorem 2, below, deals with compact sets C ⊆ R d . A first result for large parallel volumes has been obtained in [4] for compact sets C ⊆ R d , where it is shown that the volume of C r is close to the volume of its convex hull conv C r = (conv C) r . In fact, there is a constant…”
Section: Introductionmentioning
confidence: 99%
“…for all sufficiently large r. In [4] an example set C was given where this volume difference behaves like r d−3 , so the exponent here is best possible. Independently, a weaker version of (3) was shown in [7, Lemma 2], where C was assumed to be an at most two-dimensional subset of the set {0, 1} d , d ≥ 3, and the volume difference was shown to converge to zero faster than r d−2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation